Epimerization-Free Synthesis of Azo-Substituted Di- and Tripeptides by Cross-Coupling of O-Triflated Derivatives and Diazenyl Anion Equivalents - Obermayer, Wolfgang; Zhang, Kezhuo; von Hagen, Julius Fabian; Oestreich, Martin (Synthesis)
Based on our previous work, a method for the synthesis of azo-substituted small peptides through C(sp2)–N(sp2) cross-coupling between triflated peptide derivatives and N-aryl-N′-trimethylsilyldiazenes is reported. The peptide-substituted azobenzene products are formed in acceptable yields with full stereoretention at the asymmetrically substituted carbon atom despite the basic reaction medium.